A Study of the Effect of Anthropomorphism of Introductory Phrases on Tourists’ Environmentally Responsible Behaviour - Xu Lele; Wang Chao; Xu Anxin; Cheng Qian (SAGE Open)
Tourists’ environmentally responsible behaviour (TERB) is important for the sustainable development of tourist destinations. Based on social information processing theory, the article explores the mechanism of anthropomorphic/non-anthropomorphic guiding phrases on tourists’ environmentally responsible behaviours, and tests the mediating role of perceived loveliness and the moderating role of social trust. The study designed three experiments to conduct questionnaire surveys on tourists, empirically analysed 463 valid questionnaires collected, and constructed a theoretical model of the influence mechanism of guiding phrases on environmentally responsible behaviours. The conclusions of the study are as follows: (1) Compared with non-anthropomorphic guiding phrases, anthropomorphic guiding phrases are more capable of generating tourists’ environmentally responsible behaviours. (2) Perceptions of likability mediate the influence of guiding phrases on tourists’ environmentally responsible behaviour. (3) Social trust positively moderates the relationship between perceived cuteness and tourists‘ environmentally responsible behaviour. The higher the social trust, the stronger the relationship between tourists’ perceived cuteness and environmentally responsible behaviour. (4) Social trust positively moderates the mediating strength of perceived cuteness; the higher the social trust, the stronger the effect of anthropomorphism on environmentally responsible behaviour through the mediating path. The findings of this study have a positive significance and effect on enhancing the theoretical exploration and use of guiding phrases in tourist destinations and environmental enterprises.